Implikasi Penerapan Good Governance terhadap Pembangunan Berkelanjutan di Bangladesh - Austin, Diah Anggraini (Journal of Education on Social Science (JESS), 2023)
Good governance has an important role in sustainable development in Bangladesh. As a developing country, Bangladesh faces a range of economic, political, social challenges and has placed significant hope in good governance to achieve sustainable development and address development-related issues. Since gaining independence in 1971, the development process in Bangladesh has faced challenges. Bangladesh has initiated the adoption of principles of good governance to improve its poor economic, political, and social conditions and to realize sustainable development. This study aims to analyze the implications of implementing good governance on sustainable development in Bangladesh. This is a qualitative research used the literature review analysis. The study used the concept of good governance and sustainable development from the UNDP which states that good governance is a crucial prerequisite for achieving sustainable development. The findings of this study indicate that the implementation of good governance in Bangladesh is primarily influenced by external pressures. The implications of implementing good governance in Bangladesh have not been fully maximized, especially concerning principles such as participation, transparency, the rule of law, justice, and accountability.